Aerobic bacteria in buffalo semen and their antibiogram - V RAMASWAMY,; LATHA, N; GNANASUBRAMANIAN, T; MANICKAM, R (The Indian Journal of Animal Reproduction, 2023)
Atotal of29 buffalo frozen semen samples were screened and 23 microorganisms including 2 yeasts wereisolated. Sixteen organisms of the 21 bacteria isolated belonged to Gram-positive group. The antibiogram studieson 15 bacteria with 17 antimicrobial agents revealed that all the isolates were sensitive to chloramphenicol,ciprofloxacin, gentamycin and neomycin. All of them were found to be resistant to ampicillin, amoxycillin,carbenicillin, oxytetracycline and penicillin-G. A combination of streptomycin and another drug or combination ofother drugs has been suggested to control bacteria in buffalo frozen semen.
Keywords: Buffalo; frozen semen; bacteria; sensitivity; resistance